2007
DOI: 10.1007/s00534-006-1159-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria and severity assessment of acute cholecystitis: Tokyo Guidelines

Abstract: The aim of this article is to propose new criteria for the diagnosis and severity assessment of acute cholecystitis, based on a systematic review of the literature and a consensus of experts. A working group reviewed articles with regard to the diagnosis and treatment of acute cholecystitis and extracted the best current available evidence. In addition to the evidence and face-to-face discussions, domestic consensus meetings were held by the experts in order to assess the results. A provisional outcome stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
305
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(320 citation statements)
references
References 15 publications
4
305
0
11
Order By: Relevance
“…Buna karşın vakaların %15'inde hematolojik komplikasyonlar hemoliz, anemi, lökositoz, nötropeni, trombositopeni, immün trombositopenik purpura, trombositoz, asit, plevral efüzyon, fulminan hepatit, masif hepatik nekroz, uzamış kolestaz, akut taşsız kolesistit ve akut renal yetersizlik gibi komplikasyonlar bildirilmiştir (5)(6)(7)(8).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Buna karşın vakaların %15'inde hematolojik komplikasyonlar hemoliz, anemi, lökositoz, nötropeni, trombositopeni, immün trombositopenik purpura, trombositoz, asit, plevral efüzyon, fulminan hepatit, masif hepatik nekroz, uzamış kolestaz, akut taşsız kolesistit ve akut renal yetersizlik gibi komplikasyonlar bildirilmiştir (5)(6)(7)(8).…”
Section: Discussionunclassified
“…Sağ üst kadran ağrısı, ateş, sarılık, lökositoz ve karaciğer fonksiyon testi anormallikleri gibi spesifik olmayan bulguları olduğu için klinik tanı koymak zordur (3). Akut kolesistitin USG tanı kriterleri; sonografik Murphy işareti, safra kesesi duvar kalınlığının artışı (>4 mm), safra kesesinin genişlemesi, safra taşı, debris ekosu görünümünün olmaması, intra ve ekstra hepatik safra yollarında genişleme olmaması, safra kesesi etrafında sıvı birikimi, safra kesesi duvarında lineer ve strial hipoekojen görünümdür (6,8,11). Hipoalbüminemi, asit yokluğunda safra kesesi etrafında sıvı birikimi, seroza altında ödem ve intramural gaz birikimi bildirilmektedir (3,8).…”
Section: Discussionunclassified
“…Very similar sets of criteria with almost 100 % specificity have been suggested in the EAES guidelines of 2006 [2] and in the Tokyo Consensus Meeting Guidelines [6]: both can be used in clinical practice.…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…Grade 11 disease is usually characterized by an elevated white cell count; disease duration of more than 72h; and imaging studies indicating significant inflammatory changes in the gallbladder. Grade 111(severe acute choelocystitis) is defined as acute choleocystitis with organ dysfunction [6].Acute cholangitis results in presentation with the clinical findings mentioned above. Abnormalities suggestive of sepsis syndrome, including leukocytosis, are frequently observed.…”
Section: Diagnostic Workupmentioning
confidence: 99%
“…Latina women showed a higher prevalence than whites, blacks or Asians. Black women did not have a significantly higher prevalence than the white sample, other factors that appear related to the incidence of gallstones include,obesity,parity,using estrogens and diabetes mellitus [4].Mustafa I,et al reported 12 cases of acute acalculous choleocystitis(AAC) in children [5].The severity of acute choleocystitis is classified into three grades mild(grade I),moderate (grade II),and severe(gradeIII),Grade III(severe acute choleocystitis) is defined as acute cholecystitis with organ failure [6].Enteric organisms are the frequent cause of acute choleocystitis and acute cholangitis, with monomicrobial(76%) and polymicobial(24%),with anaerobes included [7].Diagnostics tests include plain roentgenograms,ultrasonography,sonographic deigns,CTscan,MRIscholangiography(endoscopic retrograde cholangiopancreatography-ERCP),HIDA(hepato-iminodiacetic acid) a functional scan test, whereas ultrasonography is an anatomic test [8,9].Empiric antibiotic regimens are aimed primarily at gram-negative bacteria.Cefazolin,ceftriaxone, and pipercillin/tazobactam are equally effective. In elderly or critically ill patient and the patient with prior common duct or complex biliary procedures, a therapeutic regimen that includes anaerobic activity is reasonable [7].Cholecystectomy remains the treatment of choice for acute choleocystitis [8].The paper reviews the diagnostic criteria, and management of acute biliary infections.…”
Section: Introductionmentioning
confidence: 99%